Dynamic analysis of photovoltaic/wind turbine hybrid micro-grid energy system - Hai, Jing (2011)
Connecting the electric grid to rural and remote areas is very uneconomical to carry out. Moreover, the utility network is not designed to fulfill the growing needs of the population and may be destabilized by new consumers. Therefore, it is more economical to electrify those areas with a micro-grid by means of existing renewable energy sources available locally. The micro-grid configuration represents the energy distribution architecture from the producing sites to consumers and eventually the interconnection between several sites and some consumers. The study of such a matrix configuration is realized using simulation tools and has to be considered from the system level with economical matters in addition to the technical aspects. As for the optimization of a hybrid micro-grid system, several models have been built to simulate and optimize hybrid systems. In this work, a quasi-dynamic model of hybrid micro-grid energy system was built use HOMER software based on a typical local household load. The optimized result was obtained under local solar/wind resources data and renewable fraction constrains. Malaysia tropical weather which has abundant solar irradiation and rich wind resource which is suitable to build a renewable energy system for most the under electrified area. According to the structure and the voltage output characteristics of the photo-voltaic array and solar panels, the framework the PV energy system simulation model is carried out. In this model, the perturb and observation method is applied to track the maximum point of the PV array power. Then the oriented vector control methods are implemented to achieve the dual closed-loop control for DC voltage and AC current, and connected to the utility grid by a three-phase PWM voltage inverter. In a real environment, the PV array temperature and solar irradiation are changing, and this has to be considered in the simulation. Since the PV energy system cannot store the excess energy, the charging and discharging characteristics of the battery are also studied and simulated. The battery storage can contribute to the stability of the PV energy system. The dynamic model of the proposed hybrid micro-grid was built in Matlab Simulink software, simulation on both grid connected operation and stand-alone operations are conducted. The series of data gained from this simulation can be a support for the real practical system, which have certain practical value.